2019
DOI: 10.1007/s11154-019-09514-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of very low calorie ketogenic diet (VLCKD) in patients with overweight and obesity: A systematic review and meta-analysis

Abstract: Introduction Obstructive sleep apnoea (OSA) is an underdiagnosed condition frequently associated with glycaemic control impairment in patients with type 2 diabetes. Aim To assess the relationship between glycometabolic parameters and OSA in obese non-diabetic subjects. Methods Ninety consecutive subjects (mean age 44.9 ± 12 years, mean BMI 42.1 ± 9 kg/m 2 ) underwent polysomnography and a 2-h oral glucose tolerance test (OGTT). Results OSA was identified in 75% of subjects, with a higher prevalence of males co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
127
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(177 citation statements)
references
References 68 publications
11
127
1
10
Order By: Relevance
“…Uric acid was finally significantly decreased, excluding a correlation between VLCKD and hyperuricemia. A recent metanalysis reported an overall neutral effect on uric acid by VLCKDs [22], and a previous study reported similar effect to ours, where a decrease in urate was observed after a VLCKD but not after an LCD [23]. These controversial results might find their explanation in timing and weight loss amplitude, as food groups that typically increase serum uric acid levels are widely consumed in ketogenic diets and might lead to such an effect in the short term [24].…”
Section: Discussionsupporting
confidence: 66%
“…Uric acid was finally significantly decreased, excluding a correlation between VLCKD and hyperuricemia. A recent metanalysis reported an overall neutral effect on uric acid by VLCKDs [22], and a previous study reported similar effect to ours, where a decrease in urate was observed after a VLCKD but not after an LCD [23]. These controversial results might find their explanation in timing and weight loss amplitude, as food groups that typically increase serum uric acid levels are widely consumed in ketogenic diets and might lead to such an effect in the short term [24].…”
Section: Discussionsupporting
confidence: 66%
“…Hyperuricaemia and dyslipidaemia are co-morbidities commonly seen in subjects seeking a KD for weight loss purposes, but they may be exacerbated by it due to the relative increase in protein intake and the variable dietary fat depending on the approach to achieve nutritional ketosis, despite not being listed as absolute contraindications according to available recommendations. However, it has been reported that both HFKD and VLCKD might lead to mild worsening short term, progressing to significant improvement or no change in most patients, possibly due to subsequent weight loss and insulin resistance amelioration in those with overweight or obesity, [56][57][58] whereas sustained hypercholesterolaemia and hypertriglyceridaemia are observed in lean subjects undergoing an HFKD for the treatment of refractory epilepsy. 59 Overall, extra caution should be paid when considering this nutritional intervention not for weight loss purposes in those with baseline metabolic abnormalities and no weight excess, or in the case of refractory epilepsy, where treatment might be considered long-term and macronutrient ratio is strongly hyper lipidic.…”
Section: Increased Serum Uric Acid and Abnormal Lipid Profilementioning
confidence: 99%
“…In humans, a KD may contribute to alleviating neurological disorders [3]. On the other hand, KD-induced persistent mild ketonemia rises low density lipoprotein cholesterol levels, potentially increasing the risk of cardiovascular disease [4], although the KD-induced rise in low density lipoprotein cholesterol levels is not unequivocally observed in all studies [5,6]. Here, we will discuss the effects of ketone bodies on cellular metabolism, and their link to pathophysiology, while also considering the impact of KB as epigenetic modulators, as there is a large and growing body of evidence demonstrating a role of KB, particularly β-hydroxybutyrate, in the regulation of chromatin histone post-translational modifications (PTMs), and thus in the transcriptional machinery.…”
Section: Introductionmentioning
confidence: 99%